The Essential Paul Gottfried: 1984-2024 - Gottfried, Paul Edward (Passage Publishing, 2025)
The Essential Paul Gottfried, Essays from 1984–2024 collects four decades of essays from one of America’s most insightful and provocative political thinkers. This collection is a testament to his intellectual rigor and courage, and showcases his remarkable ability to bring clarity to the many issues that mainstream liberals and establishment conservatives have persistently misunderstood. Wherever public discourse finds itself at an impasse to make sense of our political environment, Gottfried stands - again and again - as a rare point of light.